Investigating the Relationship between Reading Strategies and Reading Comprehension Achievement among Eleventh-Grade Students - Indry Kaseger; Virginia Gabrella Sengkey (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to figure out the level of students’ reading strategies use and the level of the students’ reading comprehension. This study was also to figure out the correlation between students’ reading strategy use and their reading comprehension. This study employed a quantitative, descriptive design to determine the levels of both variables and a correlational design to examine the correlation between them. The instrument of this study was adapted from Mokhtari and Sheorey (2002) for the survey of reading strategies and the reading comprehension section in the TOEFL Junior Standard Test to measure students’ reading comprehension. This study was conducted on 45 students of the XI grade of one of the high schools in North Sulawesi. The result showed that the students' reading strategies were in the medium level (M=3.48) and their reading comprehension was at the very least level (M=51.11). Finally, it was found that there was a significant correlation between students’ reading strategies use and their reading comprehension, as the result showed p=.022 < 0.05, r=.342. Thus, it is important for the students to be aware of the importance of reading strategies and apply these strategies to have better reading comprehension. Keywords: Students’ Reading Strategies, Students’ Reading Comprehension